Hardiness in Increasing Work Productivity (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
Productivity is a concept related to the quantity of work results based on human resources, so this study aims to analyze the influence of workload, work discipline and leadership style on work productivity through the mediation of hardiness at work. This study was conducted on 100 employees who worked for companies engaged in wood trading. Researchers collected data using questionnaires given individually and in groups conducted through work units. The data were analyzed using path analysis arranged according to theoretical hypotheses and tested by linear regression techniques with intervening variables. Path analysis is used to assess the effects of mediation according to structural models. Based on the results of the study, it was concluded that workload, work discipline and leadership style affect employee work resilience, this shows that in the company there is a need for a workload that can hone employee resilience at work, and followed by self-discipline in employees with the right leadership pattern. The results also show that resilience at work contributes significantly to productivity, this shows that it is necessary to develop self-resilience in employees to produce optimal productivity, but toughness is not a mediation of workload, work discipline and leadership style on work productivity. The results of this research can be used as a basis for companies in increasing employee work productivity through increasing resilience at work. Work hardiness in employees can be honed through a gradual increase in workload followed by discipline at work and the application of a leadership style that understands employee characteristics. Keywords: Workload, Work Discipline, Leadership Style, Hardiness, Work Productivity.